The genetic relationships and Indo-Pacific connectivity of whale sharks (Rhincodon typus) with particular reference to mitochondrial COI gene sequences from Cendrawasih Bay, Papua, Indonesia - Abdul Hamid A. Toha; MUHAMMAD DAILAMI; SAIFUL ANWAR; JUSWONO B. SETIAWAN; YUSUP JENTEWO; IDA LAPADI; SANNY SUTANTO; RATIH ARYASARI; AMBARIYANTO AMBARIYANTO; FERAWATI RUNTUBOI; HAWIS MADDUPPA (Biodiversitas Journal of Biological Diversity, 2020)
The whale shark (Rhincodon typus) inhabits Cenderawasih Bay at the Birdhead Seascape of Papua in high frequent sightings, but little is known about its genetic characteristics and connectivity. The study was conducted to characterize of the R. typus COI gene fragment from Cenderawasih Bay, in order to accurately compare with the 27 COI gene fragment sequences from the global whale shark deposited in the GenBank. A total of 28 meat samples of whale shark were collected by biopsy punch on a pole spear. The meat samples were extracted to obtain whole genome then amplified and sequenced to obtained COI nucleotides. The determined COI is a 669 bp, comprising of A = 26.5%, T/U = 30.5%, C = 28.3%, dan G = 14.7%. In total, 41 cutting sites of all the sequences ranged in size from 5-7 bp long. One COI single nucleotide polymorphisms and 2 haplotypes were identified. Single site substitution change from T to C for both haplotypes was observed. Overall, the haplotype diversity (Hd= 0.137) and nucleotide diversity (?=0.0002) were relatively low. A different nucleotide composition, number and arrangement of the sequences with the whale shark COI sequences from Cenderawasih Bay compared to COI gene fragment sequences from GenBank were observed. This study shows the availability of sequence of whale shark will contribute to aid further studies of molecular systematics, phylogeography, genetic differentiation, and conservation genetics.